Pengungkapan Corporate Sosial Responsibility dan pemilihan audit independen - Loe Davina Clarissa Lukman; Rizky Eriandani (Jurnal Ekonomi Modernisasi, 2021)
This research was conducted to know the effect of voluntary corporate social responsibility on the request for independent audit selection with company characteristics as control and to know the influence of CSR disclosure on audit fees. This research uses quantitative methods. The population in the research is manufacturing industry sector companies located on the Indonesian Stock Exchange in the period 2017 to 2019. Samples in the study amounted to 435 manufacturing industry sectors that have met the criteria as research objects. The results obtained in this study show that CSR disclosure has a significant influence on independent audit selection. CSR does not have a significant influence on audit fees. The conclusion taken from the study is that CSR disclosure variables have a significant negative on the selection of audit independent with company characteristics as control.